INTERNALISASI NILAI MODERASI BERAGAMA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 7 KECAMATAN KUALA JAMBI KABUPATEN TANJUNG JABUNG TIMUR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The diversity of Indonesian society, which includes differences in ethnicity, religion, and culture, has the potential to create conflict if it is not accompanied by mutual respect. Therefore, religious moderation becomes essential to be internalized, particularly through Islamic Religious Education (PAI) in schools. This study aims to describe the process of internalizing religious moderation values in PAI learning at SMP Negeri 7 Kuala Jambi District, Tanjung Jabung Timur Regency. This research employs a qualitative approach with a descriptive field research design. Data were collected through observation, interviews, and documentation. The results show that the internalization of religious moderation values has been implemented systematically through the integration of school policies, contextual and dialogical learning processes, and habituation in daily life. The school's efforts are carried out through policies, learning programs, and the creation of a conducive environment, while PAI teachers play roles as educators, mentors, and role models in instilling values of tolerance, justice, balance, and non-extremism. In conclusion, the internalization of religious moderation values is able to shape students’ characters to be moderate, inclusive, and respectful of differences, and requires continuous support from schools, families, and the community.